First records of the genera Aniseres Förster, 1871 and Pantisarthrus Förster, 1871 (Hymenoptera, Ichneumonidae, Orthocentrinae) from the Oriental region - Varga, Oleksandr (Zootaxa, 2026)
In this paper, two orthocentrine genera, Aniseres Förster, 1871 and Pantisarthrus Förster, 1871, are recorded from the Oriental region for the first time. Three new species are described from Vietnam: A. brevicauda sp. nov., A. vietnamensis sp. nov., and P. orientalis sp. nov.